Diagnosis of urogenital tuberculosis by multiplex‐nested PCR targeting mpt64 (Rv1980c) and IS6110: comparison with multiplex PCR and GeneXpert® MTB/RIF. (22nd June 2022) - Kamra, E.; Alam, D.; Singh, V.; Kumar, M.; Chauhan, M.; Mehta, P.K.
Abstract: A multiplex‐nested PCR (M‐nested PCR) targeting mpt64 (Rv1980c) + IS 6110 was designed to detect Mycobacterium tuberculosis ( Mtb ) DNA within urine ( n = 35), endometrial biopsies ( n = 22) and menstrual blood ( n = 3) of male/female UGTB patients, and results were compared with M‐PCR using the same targets. Detection limit of the purified Mtb DNA was found to be 1 fg by M‐nested PCR, which was 10 6 ‐fold lower than M‐PCR. Moreover, sensitivities of 100% and 81·8% were obtained in confirmed ( n = 5) and clinically suspected UGTB ( n = 55) cases, respectively, by M‐nested PCR, with a specificity of 97·1% ( n = 70). Sensitivities attained by M‐nested PCR were significantly higher ( p < 0·05) than M‐PCR in both clinically suspected and total UGTB ( n = 60) cases. To confirm the true PCR‐negative results, an internal amplification control, that is, human β‐globin gene ( hbb ) was incorporated in the M‐nested PCR/M‐PCR assays, wherein all the clinical specimens (positive/negative for mpt64 /IS 6110 ) were found to be positive for hbb . Some UGTB specimens ( n = 35) were also subjected to GeneXpert® MTB/RIF assay that revealed a significantly lower ( p < 0·001) sensitivity (17·1 vs 88·6%) than M‐nested PCR, although high specificity (100%) was attained with GeneXpert. After validating the results in a higher number of UGTB specimens, our M‐nested PCR may be translated into an attractive diagnostic kit. Abstract : Significance and Impact of the Study: We developed a multiplex‐nested PCR (M‐nested PCR) assay targeting mpt64 (Rv1980c) and IS 6110 for the diagnosis of male/female urogenital tuberculosis (UGTB) patients, which demonstrated good sensitivity and specificity. Notably, M‐nested PCR exhibited significantly higher sensitivities, as compared to M‐PCR ( mpt64 + IS 6110 ) and GeneXpert® MTB/RIF assay. After validating these data with the larger sample size, our M‐nested PCR may develop into a diagnostic kit for routine use.